The necessity of accelerated ageing in fire performance assessments of composite materials. (September 2021) - Sandinge, Anna; Blomqvist, Per; Dederichs, Anne; Markert, Frank
Highlights: Fire testing of aged materials is not dealt with in the regulations. There is a lack of knowledge regarding the effect of ageing on fire performance. Further research with the effect of ageing on the fire behaviour is needed. The identified ageing studies showed that fire properties are affected by ageing. Vital to do a validation of the accelerated ageing method with real-time ageing. Abstract: The market for lightweight fibre reinforced polymer (FRP) composites is growing. This is seen within advanced applications for e.g. aeronautics, modern ship vessels and railway vehicles. FRPs are often used to save weight, but the downside is that they are ignitable, which implies a potential higher fire risk. It is thus important to thoroughly characterise the material properties of FRPs, including the fire performance, in order to ensure a high safety level. Fire performance testing is made with newly produced materials to show the conformance to required standard test. However, the impact of ageing on the fire performance of materials and products is not mandatory information and hardly ever known. This is still an overlooked matter that is important to address for combustible materials in transport applications, where the requirements of personal safety are especially high. Accelerated ageing is a method to expose materials and products to various environmental parameters for a simulation of long-term usage. Within a few days, weeks or months the damage and degradation of the materials can occur, which normally would be after years in normal climate and after normal usage. Fire performance testing of test samples subjected to accelerated ageing would potentially give important information on the long-term safety of the end-use application of FRPs. The objective of this paper is twofold. One is to find out if the industry, society and research need to deal with the effect of ageing on materials in relation to fire safety as this is not dealt with in fire regulations. And further to identify the state-of-the-art of accelerated ageing methods relevant for Fibre Reinforced Polymer (FRP) materials. In summary, the findings in the literature were limited of reported ageing effects of FRPs, with respect to the fire behaviour. An important conclusion is that there is a major lack of knowledge regarding material aging and fire behaviour, especially for FRPs. However, the identified ageing studies showed that both fire and mechanical properties were affected by ageing. The accelerated ageing methods described in literature was not consequently applied. The ageing methods were special designed for each study and application of material. All methods need a proper validation applying real time ageing.